Situation Report: Hungary, 1 August 1980 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe/Radio Liberty based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Lack of Small-Scale Industry a Hindrance to Economic Progress Correspondence Courses for Laymen at the Budapest Theological Academy Many Foreigners Attend Hungarian "Summer Universities" University Admission - A Hotbed of Conflict Seniority and Its "Rewards" Mrs. Kadar Retires: A Modest First Lady